Impact of contract farming on green technological efficiency of farmers: a comparative study of two contract organizational models - Li, Qi; Wang, Zixuan (Frontiers in Sustainable Food Systems, 2024)
Introduction: Engaging in contract farming represents a crucial avenue for developing countries to integrate small farmers into modern agricultural practices. Existing research believes that contract farming offers a promising opportunity for fostering sustainable agricultural development. However, insufficient attention has been directed towards investigating the varying impacts of different organizational models within contract farming on farmers' transition to green production practices. . Methods: This study investigates the impact of contract farming on green technological efficiency of farmers using survey data from 719 wheat growers in Shandong Province, China. The propensity score matching method and multiple mediation effects models are employed for empirical analysis. Results: The organizational model plays a pivotal role in determining whether participation in contract farming can improve the green technological efficiency of farmers. Participation in an integrated model demonstrates a significant effect on improving green technological efficiency, whereas participation in a quasi-integrated model does not show a significant improvement. Integrated contract farming can improve green technological efficiency through expanding the degree of land consolidation and enhancing the level of productive service, whereas quasi-integrated contract farming improves green technological efficiency only by enhancing production intensification. As an economic incentive measure, the effect of contract purchase price on strengthening the enhancement of green technological efficiency in the quasi-integrated model is moderate only when the contract purchase price exceeds the local average selling price of wheat by more than 19.3%. Conversely, the moderate effect of farmers' dividend income in the integrated model remains consistent, with higher dividend incomes correlating with a stronger moderating effect. Discussion: The impact of contract farming on green technology efficiency correlates significantly with the organizational model. Compared with the quasi-integrated contract farming model, the integrated model distinctly excels in advancing farmers' green technology efficiency, evidenced by its ability to consolidate fragmented land, provide productive services, and offer economic incentives. Therefore, to unlock the latent potential of contract farming in driving agricultural green transformation, a shift towards organizational models with higher levels of integration is essential.